Activated Rho Kinase Mediates Diabetes‐Induced Elevation of Vascular Arginase Activation and Contributes to Impaired Corpora Cavernosa Relaxation: Possible Involvement of p38 MAPK Activation. (8th April 2013) - Toque, Haroldo A.; Nunes, Kenia P.; Yao, Lin; Liao, James K.; Webb, R. Clinton; Caldwell, Ruth B.; Caldwell, R. William
Abstract Introduction. Activated RhoA/Rho kinase (ROCK) has been implicated in diabetes‐induced erectile dysfunction. Earlier studies have demonstrated involvement of ROCK pathway in the activation of arginase in endothelial cells. However, signaling pathways activated by ROCK in the penis remain unclear. Aim. We tested whether ROCK and p38 MAPK are involved in the elevation of arginase activity and subsequent impairment of corpora cavernosal (CC) relaxation in diabetes. Methods. Eight weeks after streptozotocin‐induced diabetes, vascular functional studies, arginase activity assay, and protein expression of RhoA, ROCK, phospho‐p38 MAPK, p38 MAPK, phospho‐MYPT‐1Thr850, MYPT‐1 and arginase levels were assessed in CC tissues from nondiabetic wild type (WT), diabetic (D) WT (WT + D), partial ROCK 2+/− knockout (KO), and ROCK 2+/− KO + D mice. Main Outcome Measures. The expression of RhoA, ROCK 1 and 2, phosphorylation of MYPT‐1Thr850 and p38 MAPK, arginase activity/expression, endothelial‐ and nitrergic‐dependent relaxation of CC was assayed. Results. Diabetes significantly reduced maximum relaxation (Emax) to both endothelium‐dependent acetylcholine (WT + D: Emax; 61 ± 4% vs. WT: Emax; 75 ± 2%) and nitrergic nerve stimulation. These effects were associated with increased expression of active RhoA, ROCK 2, phospho‐MYPT‐1Thr850, phospho‐p38 MAPK, arginase II, and activity of corporal arginase (1.6‐fold) in WT diabetic CC. However, this impairment in CC of WT + D mice was absent in heterozygous ROCK 2+/− KO + D mice for acetylcholine (Emax: 80 ± 5%) and attenuated for nitrergic nerve‐induced relaxation. CC of ROCK 2+/− KO + D mice showed much less ROCK activity, did not exhibit p38 MAPK activation, and had reduced arginase activity and arginase II expression. These findings indicate that ROCK 2 mediates diabetes‐induced elevation of arginase activity. Additionally, pretreatment of WT diabetic CC with inhibitors of arginase (ABH) or p38 MAPK (SB203580) partially prevented impairment of ACh‐ and nitrergic nerve‐induced relaxation and elevation of arginase activity. Conclusion. ROCK 2, p38 MAPK and arginase play key roles in diabetes‐induced impairment of CC relaxation.